The Effect of Import Quotas on the Level of Local Content of Indonesian Manufactured Products - Nurul Rachmawati; Diah Widyawati (Green Publisher Indonesia, 2025)
The Indonesian government's implementation of import quotas for manufacturing raw materials serves as a strategic policy to enhance domestic industrial capacity and increase the Domestic Content Ratio (DCR). This study investigates the effect of import quota policy on DCR levels, aiming to constrain import flows and encourage import substitution industries. Using a conditional input demand function framework, the analysis evaluates DCR changes resulting from import quota implementation. Panel data from manufacturing industry companies between 2007–2013 indicate that import quotas significantly raise DCR by 6.73 percent in affected sectors. Further estimates confirm a notable DCR increase in industries influenced by the policy. However, findings reveal that domestic and imported raw materials are complementary, implying that the import quota policy does not stimulate genuine import substitution industry growth. This limitation arises from the absence of viable domestic alternatives for manufacturing-grade raw materials. Consequently, while import quotas effectively boost DCR, they fall short in fostering import substitution industrialization. Policy implications highlight that import quota effectiveness is restricted by domestic supply constraints, necessitating complementary measures focused on upstream industrial development and improvement of domestic raw material quality.